Pemahaman serta Pengenalan Metode Kasir Pos Thermal dalam Perhitungan Penjualan - Risa Amelia; Ruth Kadesy Kasih; Ahmad Batara Indra Marangga; Ladiva Nur Patricia; Ahmad, Ahmad (Journal of Community Service and Engagement, 2026)
This study discusses the outcomes of an activity focused on improving understanding and introducing the thermal POS cashier method in sales calculation for micro, small, and medium enterprises. The activity was designed as part of a community-based academic program aimed at strengthening administrative and transactional capabilities of local businesses. The implementation process involved direct assistance, practical demonstrations, and continuous guidance in operating thermal POS systems. The results show that participants experienced improved accuracy in sales recording, faster transaction processing, and better organization of financial data. The achieved outputs include a final group report, a scientific article, media publication, an innovation poster, and a comprehensive activity video, which collectively represent both academic accountability and practical impact. These outputs also serve as documentation, dissemination tools, and references for further development programs. The introduction of thermal POS systems proved effective in supporting business efficiency and promoting digital awareness among small-scale entrepreneurs. The findings highlight the importance of integrating simple technological solutions into community empowerment initiatives to enhance sustainability and competitiveness of small enterprises.